2016
DOI: 10.1080/10942912.2016.1166128
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of multi-floral honey from the West Bank, Palestine

Abstract: Honey is a nutritious product that is produced by honey bees. Its nutritional value and genuine quality is of great importance to consumers. The present study aimed at evaluating the physico-chemical properties of Palestinian multi-floral honey from the West Bank. For this purpose, a total of 33 honey samples were collected directly from honey beekeepers in different geographic regions of the West Bank and analyzed for pH, moisture, relative density, total sugars, reducing sugars, sucrose, fructose, proteins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 37 publications
9
43
9
1
Order By: Relevance
“…This results confirm that sugars were important and they are a major constituents of honey 3 . This results were similar with the report from Benin, 60-70% 3 and Brazil, 67.6-72.4% 30 , but lower than reported in Palestine study (the mean value of 78.86% 2 and Cameroon (77.9-83.1%) 31 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This results confirm that sugars were important and they are a major constituents of honey 3 . This results were similar with the report from Benin, 60-70% 3 and Brazil, 67.6-72.4% 30 , but lower than reported in Palestine study (the mean value of 78.86% 2 and Cameroon (77.9-83.1%) 31 .…”
Section: Resultssupporting
confidence: 92%
“…Honey is frequently used for nutritional, medicinal and industrial purposes, and it is important commodity in international market 1 . More importantly, honey possess antibacterial properties 2 . It is also use in the treatment of cardiovascular diseases, cancers, cataract and several inflammatory diseases, as well as, wound healing 3 .…”
Section: Introductionmentioning
confidence: 99%
“…On Day 0, the TSS value for G. thoracica honey was 70.5±0.1 °Brix. Previous studies found that the TSS value for stingless bee honey from Malaysia was in the range of 60.85-72.25 °Brix [27] and these values were slightly higher (71.1 to 74.7 °Brix) for stingless bee honey from Brazilian semiarid region [23]. The variation of TSS value between Malaysia and Brazil honey might be affected by the type of stingless bees as well as climatic and geographic factors [28].…”
Section: Resultsmentioning
confidence: 90%
“…Glass cell filled with samples was then ready to be measured for the color parameter. According to Reference [23], the colour intensity of G. thoracica stingless bee honey was measured using the Pfund method; honey was diluted to 50g/100ml (w/v) in ultrapure water. The absorbance of the honey was determined using UV-VIS spectrophotometer at 636 nm and then converted to the Pfund scale according to the Equation (2): mmPfund = -38.7 + 371.39xAbs…”
Section: ) Colour Parameter and Color Intensitymentioning
confidence: 99%
“…The water content of honey determines its stability and quality (Abdulkhaliq and Swaileh, 2017). The most suitable would be to store honey containing less than 18% water without a risk of fermentation, although the ordinance provides for up to 20% (Bilić, 2013).…”
Section: %mentioning
confidence: 99%